What Conceptual Metaphors Appear in Texts on Psychedelics and Medicine? Corpus-Based Cognitive Study - Bryła, Milena (Respectus Philologicus, 2022)
This paper aims to present conceptual metaphors employed to discuss psychedelics in texts published online by organizations popularizing knowledge about psychedelic substances. The foundation of this investigation comprises Cognitive Grammar, Conceptual Metaphor Theory, and Corpus Linguistics. A corpus of 160 texts on medical research, mental health, and therapy published in 2020 is built to enable quantitative and qualitative analysis. The investigation reveals the existence of the conceptual metaphors: psychedelic experience is a trip (a single experience that requires return and may involve adventurous, sacred, challenging aspects), the psychedelic experience is a journey (a set of experiences (trips), integration process, and development, may involve healing), the psychedelic substance is a tool / bridge / vehicle / agent providing access. The study of collocates of the word “psychedelic” also suggests the conceptualization of the psychedelic substances and/or experience as medicine in the analyzed corpus.